Fathers’ involvement in pregnancy and childbirth in Africa: an integrative systematic review - Samuel Nambile Cumber; Anna Williams; Helen Elden; Malin Bogren (Global Health Action)
Background As notions of masculinity evolve globally, it is important to understand their dimensions within geographic regions and life contexts. African men’s involvement in their partners’pregnancy and childbirth has been explored to a limited extent in the peer-reviewed literature. This analysis provides a comprehensive examination of the existing literature on the diverse experiences of fathers across the African continent. Aim This study aims to provide an overview of fathers' experience of involvement in their partners’ pregnancies andchildbirth in Africa. Methods A systematic integrative literature review guided the process. The review comprised problem identification, literature search, data evaluation, data analysis and presentation of results. Systematic searches were conducted in the Cinahl, PubMed and Scopus databases. Results The search identified 70 articles of which 31, relating to 11 African countries, were used. Of these, 20 were qualitative, 9 were quantitative and 2 were mixed-methods studies. Men’s alienation from health services, and traditional gender norms that discourage fathers’ supportive role during pregnancy were prevalent themes. Financial pressures also dominated fathers’experiences. At the same time, in 18 studies fathers expressed motivation to be involved partners and supportive fathers, despite stigma and exclusion from maternity services. Conclusion This integrative review shows that fathers’ experiences of their involvement in their partners’ pregnancy and childbirth across African countries are influenced by multiple factors. While unwelcoming health services, traditional gender norms, and low income are barriers to male involvement, education, younger age, and modern gender norms are associated with greater male involvement.